Variation in fungal microbiome (mycobiome) and aflatoxin in stored in-shell peanuts at four different areas of China - Ding, Ning; Xing, Fuguo; Liu, Xiao; Selvaraj, Jonathan N.; Wang, Limin; Zhao, Yueju; Wang, Yan; Guo, Wei; Dai, Xiaofeng; Liu, Yang (Frontiers in Microbiology, 2015)
The contamination of peanuts with Aspergillus sp. and subsequently aflatoxins is considered to be one of the most serious safety problems in the world. Mycobiome in peanuts is critical for aflatoxin production and food safety. To evaluate the biodiversity and ecological characteristics of whole communities in stored peanuts, the barcoded Illumina paired-end sequencing (BIPES) of the internal transcribed spacer 2 (ITS2) region of rDNA was used to characterize the peanut mycobiome monthly over a period of one year at four main peanut grown areas i.e Liaoning (LN, North East), Shandong (SD, East), Hubei (HB, Central) and Guangdong (GD, South) provinces. The fungal diversity of peanuts stored in SD was the highest with 98 OTUs and 43 genera, followed by LN, HB and GD. In peanuts stored in SD, Rhizopus, Emericella and Clonostachys were predominant. In peanuts from LN, Penicillium, Eurotium and Clonostachys were abundant. In peanuts from HB, Penicillium, Eurotium and Aspergillus were higher. In GD peanuts, Eurotium, Aspergillus and Emericella were mainly seen. The abundances of Aspergillus in LN, SD, HB and GD were 0.53%, 6.29%, 10.86% and 25.75%, respectively. From the North of China to the South, that increased over the latitude, suggesting that the higher temperature and relative humidity might increase the risk of peanuts contaminated with Aspergillus and aflatoxins. During the storage, Aspergillus levels were higher at 7-12 months than in 0-6 months, suggesting that the risk increases over storage time. At 7-10 months, AFB1 was higher in four areas, while declined further. The reduction of AFB1 might be attributed to the inhibition and degradation of AFB1 by A. niger or to the combination with the compounds of peanuts. This is the first study that identified the mycobiome and its variation in stored peanuts using ITS2 sequencing technology, and provides the basis for a detailed characterization of whole mycobiome in peanuts.